Constructing and Validating a Multiple-Indicator Construct of Economic Hardship in a National Sample of Adolescents with Disabilities. (July 2015) - Murray, Christopher; Doren, Bonnie; Gau, Jeff M.; Zvoch, Keith; Seeley, John R.
The purpose of the current study was to develop a multi-indicator construct of economic hardship among adolescents with disabilities ( N = 9, 230) participating in the National Longitudinal Transition Study–2, the largest, most comprehensive investigation of adolescents with disabilities ever conducted. Five theoretically relevant indicators (i.e., family income, head-of-household education, head-of-household employment, participation in social programs, and lack of resources) contributed to the formation of an economic hardship latent construct. Scores on this factor were validated through associations with demographic, tangible-resource, school, and family factors. The implications of these findings for continued efforts to understand and respond to economic hardship among adolescents with disabilities are discussed.